Idea zarządzania w administracji publicznej - Sudoł, Tomasz (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Changes in the legal system and admission of Poland to the EU structures caused a dramatic increase of the significance of the local government administration in Poland. Public management as a new field of management sciences is characterized with its own specificity resulting mainly from the letter of law. And the significance of such management results mainly from the access to the EU aid resources, of which the Polish local governments are the main consumers. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 174-181